The evaluation and justification of the effectiveness of 4D CAD using multi-criteria analysis - Reizgevicius, Marius; Ustinovichius, Leonas; Simanaviciene, Ruta; Rasiulis, Romas; Peliksa, Mykolas (Journal of Civil Engineering and Management, 2014)
The article presents the results of the analysis focused on the effectiveness of 4D CAD the phenomenon of which has been analysed by foreign scientists considering a number of different aspects. The conducted research differs from prior literature as the objective, in our case, was to evaluate effectiveness and justify results using multi-criteria analysis. Effectiveness has been investigated through the construction experiment observing group performances applying two different types of information – 2D CAD and 4D CAD drawings. Research findings have proved that the efficiency of using the 4D model has been doubled given the same time constraints when the evaluating the completeness of the construction object. Research results have also showed that the use of the 4D model helped with completing the construction of the object much faster. A comparison of the results of the participants of two groups has revealed that the use of the 4D CAD model has twice reduced the occurrence of mistakes in the construction process and helped the participants with faster detecting and fixing the errors they made. TOPSIS, SAW and CORPAS multifunctional solution making methods were employed for 2D and 4D ranking during the experiment on 4D efficiency. The findings confirm that the 4D model is more rational, more convenient and efficient than the 2D model regarding all results of statistical and multi criteria analysis.